Development of My Biology App Learning Media Based on Android Materials of Food Digestion Systems as Student Learning Source at Senior Hight School (Universitas Negeri Semarang, 2021)
The implementation of the curriculum of 2013 entrusts of innovative and creative learning with the integration of technology in the learning process. Teachers should be creative in finding and gathering learning resources, as well as making teaching materials needed in learning that can help students in learning to achieve goals in the curriculum. So it is necessary to develop learning media based on My Android Biology App in schools in learning biology. Especially in the food digestive system material can be motivate the student and the result of learning. The aim of this study is (1) to analyze the validity of the My Biology App according to media experts and material experts, (2) to analyze the feasibility of the my biology app according to teacher and student responses, (3) to analyze student learning motivation and (4) to analyze the result of learning at student. The method of research is Research and Development (R & D). Pre-Posttest Control Group is the research design. The results of the validation from media experts and material experts indicate that the learning media My Biology App is very valid. It appears in teacher responses with an average of 97.62 and student responses with an average of 108 with a percentage of 90% suitable for use in learning activities. The effectiveness is determined from the motivation data and student learning outcomes. 63% of students are highly motivated and 37% are motivated. The results of the posttest in the experimental class with an average of 86.96 greater than the posttest in the control class with an average of 83.25. In addition, the n-gain in the experimental class 0.74 is greater than the control class with an n-gain of 0.70. It can be concluded based on the results of research that the learning media My Biology App can increase motivation and student learning outcomes in the food digestive system material.